Approximation Properties of a New Type of Gamma Operator Defined with the Help of k-Gamma Function - Gurhan Icoz; Seda Demir (Journal of Function Spaces)
With the help of the k-Gamma function, a new form of Gamma operator is given in this article. Voronovskaya type theorem, weighted approximation, rates of convergence, and pointwise estimates have been found for approximation features of the newly described operator. Finally, numerical examples have been provided to demonstrate that the operator is approaching the function.